Social workers' experiences of psychological consultation on high risk youth: Helpful, unhelpful, and mediating elements. (April 2023) - Sproull, Alan J; Johnson, Dan
Psychological consultation is a key means of informing care and practice with psychological theory and evidence. The current paper sought to investigate what elements of psychological consultation are useful for social workers when consulting on high-risk youth, due to the current gap in the literature. Seven social workers shared their experiences during one-to-one interviews. The data was analysed through thematic analysis and the emerging themes were organised into three categories: Helpful elements, such as a safe space, independent expertise, and a shared understanding; Unhelpful elements, including consultee anxiety and the unheard young person; A Mediating element in the form of feasible recommendations. The implications of these findings are discussed, as well as the limitations of this paper and recommendations for future research.